Instrumentation and process measurements - William Bolton (1933- (Longman, 1991)
The book gives an overview of instrument systems, followed by a kook at the constituent elements of such systems, a discussion of measurement systems for process variables and the maintenance of instrument systems. All chapters include worked examples and problems, with answers appearing at the end of the book